2018
DOI: 10.1039/c8ew00497h
|View full text |Cite
|
Sign up to set email alerts
|

Extending the dynamic range of biochemical oxygen demand sensing with multi-stage microbial fuel cells

Abstract: With multi-stage MFCs the dynamic sensing range for BOD can be significantly increased allowing for monitoring of higher strength wastewaters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…In this study, a multi-stage MFC was used as reactor for the detection of acute toxic events. The multi-stage MFCs offer the advantage of measuring BOD concentration over a large range (Spurr et al, 2018) exhibiting a positive correlation between current generation and BOD while also allowing the presence of toxic compounds to be detected due to loss of current. The large range of BOD concentrations was possible due to the multi-stage array able to use unconsumed substrate in downstream MFCs (as previously reported by Spurr et al, 2018).…”
Section: Specificity Of a Multi-stage Mfc As Toxicity Biosensormentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, a multi-stage MFC was used as reactor for the detection of acute toxic events. The multi-stage MFCs offer the advantage of measuring BOD concentration over a large range (Spurr et al, 2018) exhibiting a positive correlation between current generation and BOD while also allowing the presence of toxic compounds to be detected due to loss of current. The large range of BOD concentrations was possible due to the multi-stage array able to use unconsumed substrate in downstream MFCs (as previously reported by Spurr et al, 2018).…”
Section: Specificity Of a Multi-stage Mfc As Toxicity Biosensormentioning
confidence: 99%
“…The multi-stage MFCs offer the advantage of measuring BOD concentration over a large range (Spurr et al, 2018) exhibiting a positive correlation between current generation and BOD while also allowing the presence of toxic compounds to be detected due to loss of current. The large range of BOD concentrations was possible due to the multi-stage array able to use unconsumed substrate in downstream MFCs (as previously reported by Spurr et al, 2018). The hydraulic connection between MFCs leads to a gradient of chemical conditions through the MFC stages which modifies the electrochemical performance of each MFC and so could modify the detection of toxic compound.…”
Section: Specificity Of a Multi-stage Mfc As Toxicity Biosensormentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty percentage of the anode compartment was inoculated with the effluent of an MFC running in the laboratory over a year using glucose and acetate as carbon sources. The bacterial community of the inoculum was dominated by Geobacter (Spurr et al, 2018). Anode medium consisted of 50 mM phosphate buffer (PBS), 1 g L −1 of sodium acetate, 25 mL L −1 of macronutrients solution, 1 mL L −1 of micronutrients solution, and 0.5 mL L −1 of vitamins solution (see composition in Table S1).…”
Section: Mfc Set Up and Operationmentioning
confidence: 99%
“…A multistage MFC possesses unique attributes because the unconsumed substrate from the front MFC flows to the subsequent MFC, where the bacteria can continuously consume residual substrate [23]. Such system was applied as a BOD sensor, and results indicated that a wide range of BOD concentrations were obtained [23]. The present study developed a three-stage SCMFC biosensor to increase the range of Cr(VI) measurements in continuous mode.…”
Section: Introductionmentioning
confidence: 99%